Analisis Efektivitas Instrumen Hukum Lingkungan dalam Pembangunan Berkelanjutan di Indonesia - Deny M. Ramdhany; Budiono; Dedi Junaedi; Jeny Mellysa Ariyanti; Edy Santoso; Nugraha Pranadita (SIYASI: Jurnal Trias Politica, 2023)
Regulatory reforms in Indonesia including the Environmental Protection and Management Law, the risk-based licensing regime, and Government Regulation 22/2021create both opportunities and challenges for achieving sustainable development. This article analyzes the effectiveness of environmental law and maps its realization from upstream instruments (Strategic Environmental Assessment/SEA and Environmental Impact Assessment/EIA) to downstream mechanisms (monitoring and multi-track enforcement). The study employs a normative legal method with statutory, conceptual, and case approaches, complemented by a policy-evaluation lens that links process indicators (EIA quality, public participation, oversight, administrative sanctions) to outcome indicators (ambient quality, land-cover change, pollution events). Findings indicate that: (i) post-approval oversight and progressive administrative sanctions strengthen compliance; (ii) high-quality EIA and meaningful participation enhance decision legitimacy and reduce dispute costs; (iii) information transparency reinforces accountability and scientific proof; (iv) civil and criminal tracks remain necessary for severe violations, while the polluter-pays principle and strict liability are effective if supported by robust damage-valuation guidance; (v) SEA functions as an upstream policy guardrail; and (vi) anti-SLAPP and citizen-lawsuit avenues broaden access to justice. The article’s novelty lies in an integrated evaluation framework that connects participation, transparency, and enforcement to measurable biophysical outcomes. Policy implications emphasize risk-based compliance assurance, strengthened environmental forensic laboratories, the use of remote sensing, independent audits, and routine public performance reporting across jurisdictions to drive continuous improvement